Vascular dysfunction induced by hypochlorite is improved by the selective phosphodiesterase-5-inhibitor vardenafil - Radovits, Tamás; Arif, Rawa; Bömicke, Timo; Korkmaz-İçöz, Sevil; Barnucz, Enikő; Karck, Matthias; Merkely, Béla; Szabó, Gábor (European journal of pharmacology, 2013)
Reactive oxygen species, such as hypochlorite induce oxidative stress, which impairs nitric oxide (NO)-cyclic guanosine monophosphate (cGMP) signalling and leads to vascular dysfunction. It has been proposed, that elevated cGMP-levels may contribute to an effective cytoprotection against oxidative stress. We investigated the effects of vardenafil, a selective inhibitor of the cGMP-degrading phosphodiesterase-5 enzyme on vascular dysfunction induced by hypochlorite. In organ bath experiments for isometric tension, we investigated the endothelium-dependent and endothelium-independent vasorelaxation of isolated rat aortic rings using cumulative concentrations of acetylcholine and sodium nitroprusside (SNP). Vascular dysfunction was induced by exposing rings to hypochlorite (100-400 µM). In the treatment groups, rats were pretreated with vardenafil (30 and 300 µg/kg i.v.). Immunohistochemical analysis was performed for the oxidative stress markers nitrotyrosine, poly(ADP-ribose) and for apoptosis inducing factor (AIF). Exposure to hypochlorite resulted in a marked impairment of acetylcholine-induced endothelium-dependent vasorelaxation of aortic rings. Pretreatment with vardenafil led to improved endothelial function as reflected by the higher maximal vasorelaxation (Rmax) to acetylcholine. Regarding endothelium-independent vasorelaxation, hypochlorite exposure led to a left-shift of SNP concentration-response curves in the vardenafil groups without any alterations of the Rmax. In the hypochlorite groups immunohistochemical analysis showed enhanced poly(ADP-ribose)-formation and nuclear translocation of AIF, which were prevented by vardenafil-pretreatment. Our results support the view that cytoprotective effects of PDE-5-inhibitors on the endothelium may underlie the improved endothelial function, however, a slight sensitisation of vascular smooth muscle to NO was also confirmed. PDE-5-inhibition may represent a potential therapy approach for treating vascular dysfunction induced by oxidative stress.
Gesehen am 13.12.2021